Understanding Alzheimer's disease - Cutler, Neal R.; Sramek, John J. (Jackson : University Press of Mississippi, 1996)
Presents information about Alzheimer's disease, explaining the basic biology of the disease, describing the course of Alzheimer's and its related behaviors and medical problems, and discussing the care of affected individuals and the search for a cure.
Includes bibliographical references (p. [121]-134) and index.
Library Journal.
Science Books & Films (A.A.A.S.).
Wilson's Public Library.
Library Journal, November 1996.
Science Books & Films (A.A.A.S.), May 1997.
Keywords: Alzheimer's disease; Alzheimer's disease